TRANSFORMASI MODEL PENDIDIKAN PESANTREN BERBASIS KITAB KUNING KE DIGITAL PLATFROM (Studi di Pondok Pesantren Al-Ma’ruf Kendal, Dander, Bojonegoro) - Agus Moh. Sholahuddin; Saeful Anwar (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
The pesantren education model still maintains the tradition of learning the yellow book, the learning methods used are Sorogan, Bandongan and Weton. in the educational model so that it continues to exist in society, therefore Islamic boarding schools need to experience a shift in this research so that they can become examples of other Islamic boarding schools. The method used in this research is qualitative research. The purpose of this study was to describe the transformation of the yellow book-based Islamic boarding school education model into a digital platform at the Al-Ma'ruf Islamic boarding school, Kendal Village, Dander District, Bojonegoro Regency. This research was conducted on July 6, 2022. Data collection techniques used interviews to find out the transformation of the yellow book-based Islamic boarding school education model into a digital platform at the Al-Ma'ruf Islamic boarding school, as well as additional data in the form of observation and documentation. Data analysis in this research uses data triangulation. The results of this study examine the transformation of the Islamic boarding school education model based on the yellow book at the Al-Ma'ruf Islamic Boarding School, where formerly the kyai recited the yellow book, only carried out by students in the Islamic boarding school environment. the general public through digital platforms such as YouTube, Facebook, and Instagram. Factors that influence this transformation are the leadership of the kyai and modernization which is marked by the swift flow of information and the encouragement of students and alumni. The inhibiting factor is the conservative view of some people that the educational model applied is the best and does not need to be changed anymore